Metodología de control para el análisis de alérgenos de leche, soja y huevo en productos cárnicos y farináceos - Cellerino, Karina (2016)
In Argentina the mandatory declaration of allergens in food labels is under revision. There is a need of methodologies that enables the detection of allergenic proteins in food. The aim of this study was to evaluate and develop methodologies that allow the detection of most important allergenic proteins in our country. Different methodologies for the detection of milk, soy and egg proteins in meat products and soy and egg protein in farinaceous products were evaluated and developed. SDS-PAGE, immunoblotting and different commercial ELISA kits were evaluated and competitive enzyme immunoassays were developed and validated. According to the results obtained it is concluded that the method to be used depends on the allergen to be detected and/or quantified, the food matrix and the treatment that was applied to the food. Some of the methods that have been studied are useful as screening methods (immunoblotting or competitive enzyme immunoassays). Positive results of these tests confirm the presence of the allergenic substance, however when the results of these methods are negative it is necessary to use a commercial ELISA kit of proper sensitivity for the allergen and the matrix to be analyzed.